The impact of primary school investment reallocation on educational attainment in rural areas of the People's Republic of China - Tobias Haepp; Lidan Lyu (Asian Development Bank Institute (ADBI), 2018)
In this paper we analyze the effect of removing village-level primary schools and effectively merging these into larger township-level schools on educational attainment in rural areas of the People's Republic of China (PRC). We employ individual- and village-level information from the China Household Ethnic Survey (CHES), which covers regions that are intensively affected by the removal campaign. We find a negative effect of school removals on primary school and junior high school completion rates. However, we also find positive effects on educational attainment beyond junior high school for those students who began their education in the new merged primary schools. This effect can be attributed to resource pooling and higher teacher quality in the new schools. The adverse effects are more severe for girls, especially if the new schools do not provide boarding and are located far away from student residences, and for children whose parents have low educational attainment, thus exacerbating gender inequality and the intergenerational transmission of education inequality. Our findings provide an important reference for other developing countries that will need to reallocate primary school investment in the future.
Keywords: H52; I21; I24; J62; 330; primary education; school removals; educational attainment; People's Republic of China